2010
DOI: 10.1177/1741143209359713
|View full text |Cite
|
Sign up to set email alerts
|

No Teacher Left Behind: Subject Leadership that Promotes Teacher Leadership

Abstract: This article presents some of the findings derived from a two-year qualitative study compromised of 51 semi-structured interviews with principals, subject leaders and classroom teachers belonging to three private K-12 schools in Beirut, Lebanon. In the context of investigating teacher leadership, this study highlights the aspects of the role of subject leaders in establishing and nourishing teacher leadership in their departments, particularly, three salutary research findings that portray how subject leaders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 15 publications
3
59
0
4
Order By: Relevance
“…This is also echoed in many of the more contemporary empirical pieces (e.g., Fairman and Mackenzie, 2015;Huang, 2016;Yow and Lotter, 2016 a) School Culture The reviewed studies revealed that certain key attributes of school culture were conducive to teacher leadership development (e.g., Beachum and Dentith, 2004;Ghamrawi, 2010;Muijs and Harris, 2006). These included a shared sense of purpose, a shared commitment to student learning, purposeful collaboration and collegiality, a desire for lifelong learning, and teacher empowerment (e.g., Cooper et al, 2016;Ghamrawi, 2010). For instance, Muijs and Harris (2006) suggested that authentic teacher leadership could only be only fostered in a supportive and collaborative school culture where the interpersonal relationships are mutually reinforcing and positive.…”
Section: Enactment Of Teacher Leadershipmentioning
confidence: 89%
See 1 more Smart Citation
“…This is also echoed in many of the more contemporary empirical pieces (e.g., Fairman and Mackenzie, 2015;Huang, 2016;Yow and Lotter, 2016 a) School Culture The reviewed studies revealed that certain key attributes of school culture were conducive to teacher leadership development (e.g., Beachum and Dentith, 2004;Ghamrawi, 2010;Muijs and Harris, 2006). These included a shared sense of purpose, a shared commitment to student learning, purposeful collaboration and collegiality, a desire for lifelong learning, and teacher empowerment (e.g., Cooper et al, 2016;Ghamrawi, 2010). For instance, Muijs and Harris (2006) suggested that authentic teacher leadership could only be only fostered in a supportive and collaborative school culture where the interpersonal relationships are mutually reinforcing and positive.…”
Section: Enactment Of Teacher Leadershipmentioning
confidence: 89%
“…Sources of influence can be grouped into two broad categories: human capital and social Regarding the methods of influence, York-Barr and Duke (2004) concluded that teacher leaders primarily influence others through 'developing trusting relationships' and 'establishing professional collaboration'. This is also echoed in many of the more contemporary empirical pieces (e.g., Fairman and Mackenzie, 2015;Huang, 2016;Yow and Lotter, 2016 a) School Culture The reviewed studies revealed that certain key attributes of school culture were conducive to teacher leadership development (e.g., Beachum and Dentith, 2004;Ghamrawi, 2010;Muijs and Harris, 2006). These included a shared sense of purpose, a shared commitment to student learning, purposeful collaboration and collegiality, a desire for lifelong learning, and teacher empowerment (e.g., Cooper et al, 2016;Ghamrawi, 2010).…”
Section: Enactment Of Teacher Leadershipmentioning
confidence: 91%
“…The second study by the same author (Ghamrawi, 2010) found that subject leaders support or impede the appearance of teacher leadership in three ways: (1) creating sub-cultures of professional collaboration in which school members devise common purposes, generate energy and enjoy respectful and trusting relationships; (2) establishing bartered leadership structures through which every member in the department can act as a leader; and (3) sincerely attempting to work in a shared system of teacher appraisal and evaluation. It is through this principled leadership that subject leaders succeed in binding teachers to a common ethos of caring, concern and commitment to their departments and students.…”
Section: Educational Leadership In the Arab World 289mentioning
confidence: 99%
“…In all cases, the literature of education supervisors' role and scheme of work may be synthesized into eight areas presented in figure 2. Figure 2 suggests that the education supervisor (From: Ghamrawi (2010Ghamrawi ( , 2011Ghamrawi ( , 2013aGhamrawi ( , 2013b)) 1-Leadership role: which entails distributing leadership, creating cultures and sub-cultures conducive to learning and growth. 2-Activating role: which make the education supervisor responsible for the collaborating and catalyzing teachers to work towards enriching the curricula with all the activities that are conducive to active learning and student-centered classrooms.…”
Section: Roles Played By Supervisorsmentioning
confidence: 99%
“…To differentiate education supervision, there is a need to shift the cultural norms towards collaboration that is rooted professional growth (Ghamrawi, 2010). In the same vein, supervision should not be viewed as a single event or happening, but rather a continuous process that never sojourns (Glickman, 2009).…”
Section: Differentiated Education Supervisionmentioning
confidence: 99%